Associations between birthweight, gestational age at birth and subsequent type 1 diabetes in children under 12: a retrospective cohort study in England, 1998–2012 - Goldacre, R (Springer, 2017)
Abstract Aims/hypothesis With genetics thought to explain only 40–50% of the total risk of type 1 diabetes, environmental risk factors in early life have been proposed. Previous findings from studies of type 1 diabetes incidence by birthweight and gestational age at birth have been inconsistent. This study aimed to investigate the relationships between birthweight, gestational age at birth and subsequent type 1 diabetes in England. Methods Data were obtained from a population-based database comprising linked mother–infant pairs using English national Hospital Episode Statistics from 1998 to 2012. In total, 3,834,405 children, categorised by birthweight and gestational age at birth, were followed up through record linkage to compare their incidence of type 1 diabetes through calculation of multivariable-adjusted HRs. Results Out of 3,834,405 children, 2969 had a subsequent hospital diagnosis of type 1 diabetes in childhood. Children born preterm (<37 weeks) or early term (37–38 weeks) experienced significantly higher incidence of type 1 diabetes than full term children (39–40 weeks) (HR 1.19 [95% CI 1.03, 1.38] and 1.27 [95% CI 1.16, 1.39], respectively). Children born at higher than average birthweight (3500–3999 g or 4000–5499 g) after controlling for gestational age experienced higher incidence of type 1 diabetes than children born at medium birthweight (3000–3499 g) (HR 1.13 [95% CI 1.03, 1.23] and 1.16 [95% CI 1.02, 1.31], respectively), while children at low birthweight (<2500 g) experienced lower incidence (0.81 [95% CI 0.67, 0.98]), signifying a statistically significant trend (p trend 0.001). Conclusions/interpretation High birthweight for gestational age and low gestational age at birth are both independently associated with subsequent type 1 diabetes. These findings help contextualise the debate about the potential role of gestational and early life environmental risk factors in the pathogenesis of type 1 diabetes, including the potential roles of insulin sensitivity and gut microbiota.